Originality and plagiarism in scientific documentation and academic writing - Motlagh, Hossein Saadabadi; Abdul Samad, Arshad (Jahan Elm Institute of Higher Education, 2016)
Source citation is a necessary skill in scientific documentation and academic writing, and guarantees the originality of the composition. Inappropriate citation behaviors can lead readers to feel that the work involves plagiarism, and consequently, bring the work into disrepute. This research is an interview-based investigation of how Iranian graduate students of science and engineering cite the sources they use while writing in English as a second language, and how they view academic writing and plagiarism. To achieve these goals, this study employed qualitative procedures to address the following questions: 1) how do students view writing from other sources, and 2) how do students view textual borrowing and plagiarism? This research aimed to show how Iranian graduate students with a blend of cultural heritage of the east and academic heritage of the west form and treat writing from sources, textual borrowing, and plagiarism. The participants of this study were eight Iranian graduate students of science and engineering a university in Malaysia. The study showed that the participants had no idea of what writing from sources is and for them it was equal to copying some materials and pasting them into their own work. They did not even distinguish between summary and paraphrase. Regarding plagiarism, this study showed three groups of students: those who had no idea of plagiarism, those who had a wrong view of plagiarism, and those with a favorable view that was approved, but was different from western notion of plagiarism.